Characteristics of Backspatter on the Firearm and Shooting Hand—An Experimental Analysis of Close‐range Gunshots. Issue 1 (17th July 2014) - Kunz, Sebastian N.; Brandtner, Herwig; Meyer, Harald J.
Abstract Contact and close‐range gunshot injuries can produce bloodstains on the shooting hand and weapon. In this study, backspatter was analyzed in experimental horizontal pistol shots into blood‐filled sponges. The shooting distances were set between 0 and 45 cm. With increasing shooting distance, there was a significant decrease in the degree of backspatter. Microspatter could be detected on the weapon and shooting hand up to a shooting distance of 40 cm. They were predominantly located on thumb and index finger as well as the radial dorsal aspects of the hand. Fine spray of microspatter combined with elongated droplets in the shape of exclamation marks was found at contact and 2‐cm distance shots. An angular calculation based on the shape of the bloodstains was possible up to a shooting distance of 2 cm. No bloodstains were detected beyond 45 cm.